PERAN TELEVISI KAMPUS SEBAGAI SARANA SOSIALISASI MELALUI DUNIA PENDIDIKAN - Hari Suryanto (Problematika Hukum, 2016)
The Campus TV is a strategic forum for education and mutual relationships within the Indonesian art institutes organised by six art institutes in Indonesia under BKS-PTSI (Badan Koordinasi Seni Perguruan Tinggi Seni Indonesia). The purpose of the forum is to support the education of art and culture and also to promote values of the local wisdom using the streaming tv portal platform for the campus community and the general public. This strategy is to response the development of media and communication technology in Indonesia